ANALYSIS OF PREFERENCES AND CONSUMER BEHAVIOR OF BATIK JAMBI - Ade Titi Nofita; Yayuk Sriayudha (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
The purpose of this study is to (1) find out how consumer preferences affect the pattern of attribute batik Jambi based on the importance and benefits of the resulting products (2). Analyze how consumer preferences of batik Jambi in relation to consumer purchasing behavior. The attribute represents the elements of a product that is considered important by consumers and serves as the basis of decision-making. Activities in order to search for and examine attributes at the level of joy and the selection of the best products so that the end product is getting an actual value more than what was expected and desired continuously in this research 5 by order of the attribute that has the value of the relative importance of the largest among other color batiks, batik type of prices and the types of batik. This research population is consumers batik Jambi. Sample units are 100 people representing various respondents among groups of people. Further data will be processed and analyzed by means of a combination approach with the method of conjoint analysis with SPSS 24.